1981
DOI: 10.1139/b81-005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of position and age on leaf photosynthesis in corn (Zea mays)

Abstract: The effects of position and age of leaves on CO2 exchange rate (CER) are described for a single-cross corn (Zea mays L.) hybrid ('Harrow 691') grown at 10-h and 20-h photoperiods. The effect of leaf age is also described for barren plants grown at a 10-h photoperiod.CER of newly matured leaves increased from leaf 3 to leaf 6 (10 h) or 8 (20 h). The rates were not significantly different for leaves 6 to 13, but were lower for leaf 14, at 10 h; while the rate for leaf 10 was lower than for leaf 8 but not differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0
6

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
2
32
0
6
Order By: Relevance
“…It has recently been demonstrated that removal of ears from maize plants leads to either accelerated or comparable leaf senescence rates relative to control plants with ears (5,6). This work reconciled contrasting literature reports pertaining to the effects of ear removal or prevention of pollination on maize leaf senescence (1,3,11,14). For Brandner et al (5,6), ear removal led to a marked decrease in dry weight accumulation by above-ground plant parts, which indicated that net photosynthesis was diminished for all hybrids.…”
supporting
confidence: 79%
“…It has recently been demonstrated that removal of ears from maize plants leads to either accelerated or comparable leaf senescence rates relative to control plants with ears (5,6). This work reconciled contrasting literature reports pertaining to the effects of ear removal or prevention of pollination on maize leaf senescence (1,3,11,14). For Brandner et al (5,6), ear removal led to a marked decrease in dry weight accumulation by above-ground plant parts, which indicated that net photosynthesis was diminished for all hybrids.…”
supporting
confidence: 79%
“…Because the accumulation of photosynthate in the leaf may impair leaf functions, Allison and Weinmann (1) implied that the accumulation of carbohydrates in the leaves was related to the rapid development of senescence. Subsequently, Christensen et al (4) and Thiagarajah et al (20) using different maize cultivars, reconfirmed that bagging or removal ofears accelerated rather than delayed senescence. Using the maize hybrid, B73 x Mol 7, Christensen et al (4) confirmed that ear removal resulted in a marked decrease in photosynthetic activity (measured by dry weight accumulation of all above-ground parts).…”
mentioning
confidence: 97%
“…Apparently the presence of pods only altered the partitioning of plant constituents (7). Based on the seasonal profiles ofChl, and activities ofthe functional enzymes nitrate reductase, nitrogenase and RuBPCase, the initiation of leaf senescence was similar for podded and depodded plants (7,8).Although Moss (17) reported that the prevention ofpollination (ear bagging or removal) delayed senescence in maize, other workers (1,3,25) found such treatments accelerated leaf and plant senescence. Subsequent work (5, 6, 27) resolved this conflict by showing the response was a reflection of genotype.…”
mentioning
confidence: 99%
“…Although Moss (17) reported that the prevention ofpollination (ear bagging or removal) delayed senescence in maize, other workers (1,3,25) found such treatments accelerated leaf and plant senescence. Subsequent work (5,6,27) resolved this conflict by showing the response was a reflection of genotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation